Influence of individual and organizational factors on career advancement of academics in private institutions of higher learning in Malaysia - Arokiasamy, Lawrence (2011)
This study was conducted to investigate the influence of individual and organizational factors on career advancement of academics in private IHLs in Malaysia. This study used the Social Cognitive Career Theory (SCCT) to predict career advancement among the academics. A stratified random sampling method was used to select a population of 221 respondents from among six private IHLs. The data obtained was analyzed using descriptive analysis, Pearson product-moment and multiple regression analysis. Analyses were carried out primarily to examine the profiles of respondents and the characteristics of the individual and organizational factors, as well as factors that influence academics’ career advancement. The findings from the regression analysis indicated that there were significant relationship between the independent variables and career advancement of academics. The regression analysis revealed that six out of 10 individual and organizational variables were significant in determining academics’ career advancement. Multiple regression analysis was used to identify the best predictors of career advancement of academics. The predictors explained 59.0% of variance in career advancement. These predictors according to descending order are family support, extraversion, neuroticism, organizational support, conscientiousness, work-life balance, work experience, social network, flexi work and mentoring. Hence, it can be said that these factors contribute significantly to career advancement of academics. The study is important as it would become a platform for future research to consider aspects of career advancement and its variants. In order to improve career advancement of academics, this study has identified that it is crucial that the relevant agencies implement human resource development initiatives. This study also signals the importance of creating and sustaining a motivating work environment to ensure better career advancement among academics. Academics should also recognize the various contributors of career advancement, some of which are based on the individual and organizational factors found in this study. By knowing these factors, they can be used as inputs in the training, promotion, and advancement planning processes in order to get the right academics candidates in private IHLs. To support the findings of this study the private IHLs, it is recommended that future studies be conducted across public and private IHLs by taking into consideration other factors that may better help understand the career advancement of academics in Malaysia.